2013
DOI: 10.1111/resp.12013
|View full text |Cite
|
Sign up to set email alerts
|

Systemic corticosteroids for community‐acquired pneumonia: Reasons for use and lack of benefit on outcome

Abstract: The main reasons for administering systemic steroids were the presence of chronic respiratory comorbidity or severe clinical presentation, but therapy did not influence mortality or clinical stability; by contrast, steroid administration was associated with prolonged length of stay. Nevertheless the steroid group did not show an increased mortality as it was expected according to the initial Pneumonia Severity Index score. Influence of steroids on outcomes of CAP need to be further investigated through randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…Earlier studies involving relatively small numbers of adult patients with severe CAP [60-62], and more recently in children [63], reported a benefit of adjunctive intravenous corticosteroid therapy with respect to duration of hospital stay or mortality or both. Somewhat disappointingly, however, the promise of this adjunctive strategy has not been confirmed in one large, randomized, double-blinded, placebo-controlled trial in adults with severe CAP [64] or in another large retrospective study [65]. Although the reasons for the apparent lack of efficacy of systemic administration of corticosteroids are unknown, it is noteworthy that neutrophils are relatively insensitive to the anti-inflammatory actions of corticosteroids [66].…”
Section: Adjuvant Anti-inflammatory Strategies In Severe Pneumococcalmentioning
confidence: 99%
“…Earlier studies involving relatively small numbers of adult patients with severe CAP [60-62], and more recently in children [63], reported a benefit of adjunctive intravenous corticosteroid therapy with respect to duration of hospital stay or mortality or both. Somewhat disappointingly, however, the promise of this adjunctive strategy has not been confirmed in one large, randomized, double-blinded, placebo-controlled trial in adults with severe CAP [64] or in another large retrospective study [65]. Although the reasons for the apparent lack of efficacy of systemic administration of corticosteroids are unknown, it is noteworthy that neutrophils are relatively insensitive to the anti-inflammatory actions of corticosteroids [66].…”
Section: Adjuvant Anti-inflammatory Strategies In Severe Pneumococcalmentioning
confidence: 99%
“…While some authors advise five days of glucocorticoid treatment in critically ill patients without tapering [49-51], others recommend tapering of glucocorticoids to avoid a rebound of inflammatory markers with consecutive rebound pneumonia [37,45,46,52]. However, it has been shown that glucocorticoids given > seven days lead to a worse clinical course measured by length of stay, clinical stability and mechanical ventilation, and more systemic complications when looking at shock and cardiac arrhythmia [53]. From COPD studies, there is evidence that stopping glucocorticoids without tapering is safe without an increased recurrence rate [54].…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies and one recent randomized trial have suggested that steroids have the benefit of leading to a more rapid resolution of fever and hypoxemia and less need for mechanical ventilation [37]. Polverino and colleagues [38], in a retrospective study, found that routine steroid therapy had no benefit in patients with CAP if it was not used for another established indication. In a population of 3,257 patients with CAP, 260 received corticosteroids, generally because of chronic respiratory illness or a severe clinical presentation, but there was no benefit in mortality and there was a longer length of stay (9 versus 6 days, P <0.01).…”
Section: New Insights Into Treatment Strategiesmentioning
confidence: 99%